Savings and Credit Cooperatives, influence on socioeconomic growth, Manabi - Ecuador - Zamora Cusme, Maryuri Alexandra (2018)
This article determined the influence on the socioeconomic growth of the population of Manabí - Ecuador during the years 2014 and 2015, the financial cooperative sector has presented a growing development; and, at present, it represents a great component within the national financial system. The evidence: the stability and the economic growth of the country from the year 2000. Based on the proposed objectives, the bibliographic, non-experimental, quantitative, qualitative and field research was applied, the Delphi, deductive and analytical method was used, a descriptive and inferential analysis was carried out on the relationship between the variables. Thus, the main results were that the actions of the savings and credit cooperatives, through the services they provide to their members, are carried out in a rational manner and these have a favorable influence on the socio-economic growth of the population of Manabí, 2014 to 2015, the contribution of migrants reflected in the remittances sent; the trust given to middle class and poor economic sectors; accompanied by the spirit of solidarity of its directors with the aim of contributing to the Good Living of its members and the community in general.